Asuhan Keperawatan pada Anak Kejang Demam dengan Diagnosa Hipertermi di Ruangan Catelia RSUD Undata Provinsi Sulawesi Tengah : Nursing Care for Children with Fever Seizures with a Diagnosis of Hypertermy in the Catelia Room Undata Hospital, Central Sulawesi Province - Mosangi, Susan Cherly; Iriani, Indri; Muhammad Asrum (Jurnal Kolaboratif Sains, 2024)
Febrile seizures can be associated with epilepsy and the risk of mental retardation in children. Until now, the cause of children experiencing febrile seizures cannot be known with certainty. However, most febrile seizures can be attributed to high fever seizures that occur due to ear infections, chickenpox, tonsillitis, or flu virus infections. Fever is not only a disease but a symptom. Fever often occurs in toddlers, when the increase in body temperature reaches the highest number scale, only causing seizures in children or what are called febrile seizures. The method used in this research is a case study with a nursing care approach. The samples were pediatric patients with hyperthermia problems in cases of febrile seizures at Undata Hospital, Central Sulawesi Province.The results of research conducted for 3 days showed that the problem of febrile seizures was diagnosed as hyperthermia and the knowledge deficit was resolved. The conclusion from this research is that there is a decrease in body temperature after applying a warm water compress.